شعرِ اقبال پر فارسی ادبیات کے اثرات - Dr. Yasmeen Kauser; Dr. Shagufta Firdous; Dr. Irum Saba (Khayaban - خیابان, 2023)
Allama Muhammad Iqbal’s reputation in the subcontinent is mostly due to his Urdu poetry, but his Persian speech was by no means inferior. Persian language was not his mother tongue but because of Syed Mir Hassan’s education and training sharpened his Persian and Arabic skills. He remembered Saadi’s "Gulistan", "Bostan" verbally at the age of about twelve. Influences of the great Persian poets and philosophers are visible on the Kalam e Iqbal. Among them are the names of Bedal, Rumi, Hafiz Shirazi, Nazeri, Sheikh Mahmood Shabstri, and Sheikh Saadi. In 1915 Iqbal’s first Persian collection, was published under the name "Israr e Khudi". The love of Iqbal’s Persian language can be gauged from the fact that by 1934 against one Urdu book, "Bang Dura" six Persian poetry books were published. Iqbal’s Persian books were sent to some Iranian teachers such as Saeed Nafisi, Syed Mohammad Moheet Taba Tabai, etc. and Iqbal used to receive letters of thanks from these scholars. Khaleefa Abdul Hakeem says that some of Iqbal’s Persian Ghazals are so excellent that if they are included in the Diwan Hafiz, readers will not be able to distinguish between the words of the Iqbal and Hafiz. Iqbal was greatly influenced by classical Persian traditions of Maulana Rome, whom he called "Peer e Roomi" and he used to call himself as "Mureed e Hindi". Iranian scholars are appreciative to Iqbal’s Persian poetry and research on Iqbal in Iranian universities is going on.